Health-Related Quality of Life After Cytoreductive Surgery/HIPEC for Mucinous Appendiceal Cancer: Results of a Multicenter Randomized Trial Comparing Oxaliplatin and Mitomycin - Moaven, Omeed; Votanopoulos, Konstantinos I.; Shen, Perry; Mansfield, Paul; Bartlett, David L.; Russell, Greg; McQuellon, Richard; Stewart, John H.; Levine, Edward A. (Annals of surgical oncology, 2020)
Background This study evaluated health-related quality of life (HRQOL) using patient-reported outcomes in subjects with mucinous appendiceal neoplasms who underwent cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) as part of a randomized trial comparing mitomycin with oxaliplatin. Methods In this prospective multicenter study, 121 mucinous appendiceal cancer patients, with evidence of peritoneal dissemination who underwent CRS, were randomized to receive mitomycin (divided 40 mg) or oxaliplatin (200 mg/m 2 ) for HIPEC. The Functional Assessment of Cancer Therapy Neurotoxicity (FACT-G/NTX) questionnaire was utilized to assess HRQOL. The Trial Outcome Index (TOI) is a summary index responsive to changes in physical/functional outcomes. Repeated measures mixed models with an unstructured variance matrix were applied to assess changes in HRQOL longitudinally. Results Baseline questionnaire compliance was 95.9%. Baseline physical well-being (PWB) was independently associated with overall survival (hazard ratio 0.79, 95% confidence interval 0.66–0.96; p = 0.017). The TOI was significantly lower in the mitomycin group compared with the oxaliplatin arm at 12 weeks ( p = 0.044; score difference 6.35) and 24 weeks after surgery ( p = 0.049; score difference 5.61). At 12 weeks after surgery, declines from baseline were significant in the TOI ( p = 0.004; score decline 8.99), PWB ( p < 0.001; score decline 2.83), and FWB ( p < 0.001; score decline 3.42) in the mitomycin group but not the oxaliplatin group. Conclusions Compared with mitomycin, HIPEC perfusion with oxaliplatin results in significantly better physical and functional outcomes. With similar survival outcomes and complication rates, oxaliplatin should be considered as the chemoperfusion agent of choice in mucinous appendiceal cancer patients undergoing CRS/HIPEC.